Stability of smooth soHtary waves for the generahzed Korteweg - de Vries equation with combmed dispersion - Yin, J. L.; Інь, Дж Л. (Institute of Mathematics, NAS of Ukraine, 2011)
The orbital stability problem of the smooth solitary waves in the generalized Korteweg - de Vries equation with combined dispersion is considered. The results show that the smooth solitary waves are stable for an arbitrary speed of wave propagation.